PERLINDUNGAN HUKUM BAGI ANAK YANG MENJADI KORBAN TERHADAP PEREDARAN GELAP NARKOTIKA BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - lusia sulastri sulastri (jurnal.unprimdn.ac.id, 2018)
Two reasons for the three reasons someone can be held accountable according to Prof. G.A. Van Hamel is; people must realize that their actions according to the social order are prohibited and people must determine their will against the changes. So in many ways children have not been able to do these two things so that children cannot think long or mature in connection with their changes. This is important because many children today are victims of narcotics abuse, so they are victims of narcotics intermediaries for other people. This study will describe how large external factors are from the perpetrators to become victims of narcotics intermediaries. This is what needs to be explored considering that children are very easy to become their modus operandi. To avoid this, it is necessary to strengthen the legal system for children who are dealing with the law through criminal sanctions that do not eliminate their future as people who cannot yet be responsible for themselves. It is not intended to release the child from existing lawsuits, but the interests of the child should be a priority, so that the punishment reflects legal protection. As we know, the government needs to be wise in this regard, the government needs preventive measures to keep children away from these illicit goods by working together to work together with the world of education. On the other hand, parents can shape themselves so that they have good individual factors for seminals, perhaps become wise and childlike children, so that children become the successors of the nation and state. In this scientific work, researchers used children's book and narcotics literature which had been examined in advance by the researchers, then the researchers constructed the materials so that they were related. And this scientific work certainly can also be useful for the government, the community, parents whose children are involved in narcotics crime.